The role of ferroptosis in intervertebral disc degeneration - Fan, Chunyang; Chu, Genglei; Yu, Zilin; Ji, Zhongwei; Kong, Fanchen; Yao, Lingye; Wang, Jiale; Geng, Dechun; Wu, Xiexing; Mao, Haiqing (Frontiers in Cell and Developmental Biology, 2023)
Nucleus pulposus, annulus fibrosus, and cartilage endplate constitute an avascular intervertebral disc (IVD), which is crucial for spinal and intervertebral joint mobility.As one of the most widespread health issues worldwide, intervertebral disc degeneration (IVDD) is recognized as a key contributor to back and neck discomfort. A number of degenerative disorders have a strong correlation with ferroptosis, a recently identified novel regulated cell death (RCD) characterized by an iron-dependent mechanism and a buildup of lipid reactive oxygen species (ROS). There is growing interest in the part ferroptosis plays in IVDD pathophysiology. Inhibiting ferroptosis has been shown to control IVDD development. Several studies have demonstrated that in TBHP-induced oxidative stress models, changes in ferroptosis marker protein levels and increased lipid peroxidation lead to the degeneration of intervertebral disc cells, which subsequently aggravates IVDD. Similarly, IVDD is significantly relieved with the use of ferroptosis inhibitors. The purpose of this review was threefold: (1) to discuss the occurrence of ferroptosis in IVDD; (2) to understand the mechanism of ferroptosis and its role in IVDD pathophysiology; and (3) to investigate the feasibility and prospect of ferroptosis in IVDD treatment.